Invasive MRSA infections in neurosurgical patients – a decade of progress. (4th May 2017) - Skally, Mairéad; Finn, Caoimhe; O'Brien, David; Fitzpatrick, Fidelma; Burns, Karen; McFadden, Elaine; Fitzpatrick, Margaret; Smyth, Edmond; Humphreys, Hilary
Abstract: Background: Methicillin-resistant Staphylococcus aureus (MRSA) is an important cause of bloodstream infection (BSI), which is declining in many countries, including Ireland. However, it also causes other invasive infections, such as meningitis in neurosurgical patients. It is unclear whether the decline in MRSA BSI is reflected in other invasive infections and in specialist units. Aim: To investigate trends in the incidence of MRSA invasive infection in a national neurosurgical centre over a 10-year period. Methods: A retrospective review of neurosurgical patients with MRSA recovered from sterile sites and indicating invasive infection, according to internationally agreed definitions was conducted between January 2006 and December 2015. Rates per 10, 000 bed days used (BDU) and neurosurgical bed days used (NBDU) were calculated and trends were analysed. Results: Forty-four cases of invasive MRSA infection were identified over the study period. The majority were BSI (26, 59%) followed by ventriculitis (8, 18%). Invasive MRSA infections declined significantly from 0.52 per 10, 000 BDU (or 4.65 per 10, 000 NBU) in 2006 to 0.22 per 10, 000 BDU (or 2.04 per 10, 000 NBDU) in 2015, p  < .01, despite an increase in neurosurgical clinical activity. Half of the infections occurred in patients with no previous history of MRSA colonisation/infection. The mean length-of-stay for neurosurgical patients with invasive MRSA infections was 67 days (median 32.5 days), significantly greater for other neurosurgical patients ( p  < .01). Conclusion: There has been a significant decrease in invasive MRSA infections in neurosurgical patients, reflecting national and international trends for MRSA BSI. This indicates that infection prevention and control measures have been effective in reducing invasive MRSA infections overall, thus contributing to improved patient care.